PENGARUH CO-BRANDING TERHADAP BRAND EQUITY MEREK YANG SEDANG MENGALAMI KRISIS DENGAN BRAND REPUTATION SEBAGAI VARIABEL MEDIASI (STUDI PADA DEAR ME BEAUTY X KFC) - Wulandari, Menik; Dirgantara, I Made Bayu; Nurdianasari, Rista (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Every brand’s management must organize their marketing strategy and communication to increase the value of brand. But in practice, not all company management is able to have a good communication with customers. Dear Me Beauty is one of the brands that made mistakes in it’s communication and marketing activity, which made the brand almost boycotted by netizens. That mistake made Dear Me Beauty loss their brand reputation and brand equity. In it’s efforts to restore their reputation and brand value in crisis, Dear Me Beauty made various efforts such as making a joint brand alliance with KFC. Co – branding is considered to be one way to save the equity of brands that are experiencing a crisis, by collaborating with brand that have positive brand equity. This research was analysed using the Structural Equation Modelling (SEM) using SmartPLS. These respondents have been selected using purposive sampling technique. In this research, co – branding has a positive influence on brand reputation. Co – branding also has a positive influence on brand equity. Furthermore, brand reputation has positive influence on brand equity and brand reputation is able to has significant influence in mediating the relationship between co – branding and brand equity.